The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1016/j.ejogrb.2006.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcome in primiparae of advanced maternal age

Abstract: Maternal age is an important and independent risk factor for adverse pregnancy outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
157
3
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(184 citation statements)
references
References 27 publications
17
157
3
7
Order By: Relevance
“…Extremes of reproductive age 13,14 , women without a partner 14 , low educational level and low pregestational BMI 1,15,16 were findings shown to be risk factors for low birth weight in this population, and these findings are in agreement with data reported by various other investigators. On the other hand, the present study also showed obesity to be a protective factor, which may reflect the fact that obese women have a greater risk of developing hyperglycemic states or diabetes (gestational or type II), commonly associated with a greater gain in fetal weight.…”
Section: Discussionsupporting
confidence: 83%
“…Extremes of reproductive age 13,14 , women without a partner 14 , low educational level and low pregestational BMI 1,15,16 were findings shown to be risk factors for low birth weight in this population, and these findings are in agreement with data reported by various other investigators. On the other hand, the present study also showed obesity to be a protective factor, which may reflect the fact that obese women have a greater risk of developing hyperglycemic states or diabetes (gestational or type II), commonly associated with a greater gain in fetal weight.…”
Section: Discussionsupporting
confidence: 83%
“…However, it could not be attributed to any specific cause such as aneuploidy, as karyotyping was sent only for few women. Many of the studies have found a higher rate of aneuploidy among miscarriages in women with advanced maternal age [7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…Ma már számos közlemény [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50] : 1,32). A császármetszés gyakorisága először szülőknél és többedszer szülőknél egyaránt lényegesen magasabb a 30 éves korosztályhoz képest.…”
Section: Növekvő Veszélyek Az Anya éLetkorának Előrehaladásávalunclassified